2022
DOI: 10.1371/journal.pone.0267029
|View full text |Cite
|
Sign up to set email alerts
|

Primary care providers’ and nurses’ knowledge, attitudes, and skills regarding latent TB infection testing and treatment: A qualitative study from Rhode Island

Abstract: Background Untreated latent tuberculosis infection (LTBI) is a major source of active tuberculosis disease in the United States. In 2016, the United States Preventive Services Task Force (USPSTF) recommended that screening for latent tuberculosis infection among individuals at increased risk be performed as routine preventive care. Traditionally, LTBI management–including both testing and treatment–has been conducted by specialists in the United States. It is believed that knowledge gaps among primary care tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…A recent qualitative study regarding PCPs' knowledge and attitudes regarding LTBI care in RI confirmed that PCPs' lack confidence with all steps of the LTBI care cascade and this confidence decreases with later steps-particularly treatment initiation and completion. 21 Further formal qualitative work is needed at our clinic to confirm these findings and identify strategies to improve PCPs' knowledge and confidence. Educational efforts such as the Regional Latent TB Infection ECHO (Extension for Community Healthcare Outcomes) 22 is one existing strategy that could potentially improve LTBI management by PCPs within primary care facilities.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent qualitative study regarding PCPs' knowledge and attitudes regarding LTBI care in RI confirmed that PCPs' lack confidence with all steps of the LTBI care cascade and this confidence decreases with later steps-particularly treatment initiation and completion. 21 Further formal qualitative work is needed at our clinic to confirm these findings and identify strategies to improve PCPs' knowledge and confidence. Educational efforts such as the Regional Latent TB Infection ECHO (Extension for Community Healthcare Outcomes) 22 is one existing strategy that could potentially improve LTBI management by PCPs within primary care facilities.…”
Section: Discussionmentioning
confidence: 96%
“…Let’s consider the gaps in TB knowledge, attitude, and skills. 21 Diseases such as TB that disproportionately impact racial and ethnic minorities are often taught in a manner that does not include how racial social inequity influences pathology. Additionally, historical and sociopolitical factors that worsen health outcomes among patients are often missing in medical curricula.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies were from lower-middle-income countries [ 9 , 31 , 36 , 37 , 40 , 41 , 43 , 46 ], five were from upper-middle-income countries [ 6 , 33 , 34 , 39 , 45 ], six were from high-income countries [ 7 , 8 , 32 , 38 , 47 , 48 ] and two were from low-income countries [ 35 , 42 ]. Four studies had representatives from a mix of countries with different income levels [ 5 , 29 , 30 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies suggest they are not. 19,20 The needs and optimal strategies to integrate LTBI care into primary care have not been well studied. More than 50 years after LTBI screening and treatment were first widely recommended and implemented, 21 there is still remarkably little evidence about implementing LTBI diagnosis and treatment in primary care in North America.…”
mentioning
confidence: 99%
“…Are primary care practitioners ready? Some studies suggest they are not . The needs and optimal strategies to integrate LTBI care into primary care have not been well studied.…”
mentioning
confidence: 99%